Investigating post-apartheid black workers' barriers to career progression and the role that the intersection of race and gender plays in shaping their experiences in the banking sector - Khunyana, Siphenathi (Department of Sociology, 2026)
This study explores workplace barriers that black women encounter in the post-apartheid banking sector in relation to their career progression from junior and mid-management levels to senior leadership roles in the banking sector. The study used a qualitative research approach with semistructured interviews to understand the lived experiences of black women in the banking sector. Data was analysed thematically, drawing on intersectionality and post-colonial theory to understand the challenges that impede career growth and transitional experiences of black women. The key findings are that the perception of intergroup racism in the Western Cape maintains racial divisions among black women and further blocks black African women from easily moving up the career ladder. African women are less privy to internal information about career progression and earning potential, with intergroup racism adding to this racial, often gendered wage-gap divide. The study revealed that many black women lack strong mentorship and coaching guidance to prepare them for senior and leadership roles. This is contrary to whites and their male colleagues who rely on old forms of networking that keep them ahead of women in advancing their careers in the bank because the banking culture remains male oriented. In relation to the male-oriented organisational culture, work-life balance stood out as a key barrier for black women's career progression because many struggled to balance work pressures with household commitments. For example, black women felt that they had to choose to first grow their families and later take on demanding work commitments. However, their white and male colleagues had access to departments such as investment banking that allowed them to juggle family and work remotely, which points to the intersection of gender, race and class in limiting black women's opportunities in the banking sector. As such, thisstudy argues that race and gender, in the context of a historically white male dominated sector, remained central as barriers to advancement to mid-managerial and senior positions in the banking sector. This study therefore advocates for black women's experiences to be central to any intervention that seeks to deracialise and invest in black women's career progression in the banking sector.